2021
DOI: 10.3389/fcvm.2021.757738
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk of Incident Coronary Heart Disease Across Chronic Inflammatory Diseases

Abstract: Background: Chronic inflammatory diseases (CIDs) are considered risk enhancing factors for coronary heart disease (CHD). However, sparse data exist regarding relative CHD risks across CIDs.Objective: Determine relative differences in CHD risk across multiple CIDs: psoriasis, rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), human immunodeficiency virus (HIV), systemic sclerosis (SSc), and inflammatory bowel disease (IBD).Methods: The cohort included patients with CIDs and controls without CID in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Whether these differences reflect unique heart-lung physiology and fibrotic mediators arising in SSc warrants further study. Moreover, although several CIDs (including HIV, RA, and SLE) are associated with heightened atherothrombotic risk, HF patients with HIV had an especially high prevalence of underlying CAD; this adds to recently reported data revealing a higher rate of CAD in patients with SLE and SSc ( 33 ), and substantiates prior reports highlighting HIV's association with acute coronary syndrome ( 34 ).…”
Section: Discussionsupporting
confidence: 84%
“…Whether these differences reflect unique heart-lung physiology and fibrotic mediators arising in SSc warrants further study. Moreover, although several CIDs (including HIV, RA, and SLE) are associated with heightened atherothrombotic risk, HF patients with HIV had an especially high prevalence of underlying CAD; this adds to recently reported data revealing a higher rate of CAD in patients with SLE and SSc ( 33 ), and substantiates prior reports highlighting HIV's association with acute coronary syndrome ( 34 ).…”
Section: Discussionsupporting
confidence: 84%
“…Vascular disease is frequent in patients with SLE, and it is the major cause of death-established SLE. Vascular disease in SLE can manifest as accelerated atherosclerosis predisposing to coronary artery disease and renal disease, which are major causes of mortality [34,35]. HCQ therapy is the standard treatment for SLE, which can lead to HCQ-induced maculopathy as one of the most serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Speaking of the observed complications, interestingly, a previous study reported that inflammatory diseases promote coronary heart diseases; however, for HIV and IBD, this only occurs when the illnesses are severe[ 1 ]. Our patient had PE, which could also have been caused by the corticosteroids prescribed after her first exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…It is classified as either ulcerative colitis (UC) or Crohn’s disease (CD). Both IBD and HIV infection can coexist in the same person, although this coexistence is rarely observed; therefore, the relationship between one and the other and the impact of this relationship on the immune system are not fully understood yet[ 1 , 2 ]. However, there are speculations that the HIV-modified CD4 + lymphocyte count plays its role in altering the course of IBD alongside increasing the likelihood of opportunistic infections occurring[ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%